Structure of the Ob-Yenisei plume in the Kara Sea shortly before autumn ice formation - Osadchiev, Alexander; Zabudkina, Zinaida; Rogozhin, Vladimir; Frey, Dmitry; Gordey, Alexandra; Spivak, Eduard; Salyuk, Anatoly; Semiletov, Igor; Sedakov, Roman (Frontiers in Marine Science, 2023)
The major Siberian rivers form large river plumes in the Arctic Ocean, which govern structure of the sea surface layer at the Arctic shelf. These river plumes were explicitly studied during the warm period in summer and early autumn characterized by high river runoff and ice-free conditions. However, little is known about processes, which occur within these river plumes at the beginning of the cold season, i.e., during late autumn shortly before sea ice formation. In this study, we report in situ measurements performed in the Kara Sea in late October in 2020, 2021, and 2022. We reveal that intense convection occurs in the Ob-Yenisei plume due to heat loss from the surface layer, which is caused by transport of cold air from land to the central part of the Kara Sea. This process induces homogenization of the Ob-Yenisei plume and results in extremely sharp salinity jump (up to 10-12 at vertical distance of 1-2 m) between the plume and the subjacent seawater. This sharp gradient is not formed at the whole area of the plume except, first, at the Ob and Yenisei gulfs due to low surface salinities and the related high temperatures of maximal density and, second, at the lateral boundary of the plume due to intense horizontal mixing across the plume-sea border. As a result, autumn convection significantly modifies vertical structure of the Ob-Yenisei plume that could affect its further spreading below sea ice during winter season.